Salicin alleviates periodontitis via Tas2r143/gustducin signaling in fibroblasts - Zhang, Zhiying; Zhou, Zhiyan; Liu, Jiaxin; Zheng, Liwei; Peng, Xian; Zhao, Lei; Zheng, Xin; Xu, Xin (Frontiers in Immunology, 2024)
Cells expressing taste signaling elements in non-gustatory tissues have been described as solitary chemosensory cells (SCCs) or tuft cells. These "taste-like" cells play a critical role in the maintenance of tissue homeostasis. Although the expression of SCC markers and taste signaling constituents has been identified in mouse gingivae, their role in periodontal homeostasis is still unclear. In this study, the expression of Tas2r143, Gnat3, Plcβ2, and TrpM5 was confirmed in primary mouse gingival fibroblasts (MGFs). Moreover, salicin could activate Tas2r143, elicited taste signaling and thus inhibited LPS-induced chemokines expression (CXCL1, CXCL2, and CXCL5) in MGFs. Consistently, salicin-treatment inhibited periodontal bone loss, inflammatory/chemotactic factors expression, and neutrophil infiltration in periodontitis mice, while these effects were abolished in Gnat3 -/-mice. This study investigated gingival fibroblasts play a critical role in the maintenance of periodontal homeostasis via "SCC-like" activity. Salicin can activate Tas2r143-mediated bitter taste signaling and thus alleviate periodontitis in mouse, indicating a promising approach to the resolution of periodontal inflammation via stimulating the "SCC-like" function of gingival fibroblasts.